2014
DOI: 10.1093/mnras/stu1395
|View full text |Cite
|
Sign up to set email alerts
|

Mass and magnification maps for the Hubble Space Telescope Frontier Fields clusters: implications for high-redshift studies

Abstract: Citation for published item:i h rdD tF nd t uz D wF nd vimousinD wF nd tulloD iF nd gl¡ ementD fF nd i elingD rF nd unei D tFE F nd etekD rF nd x t r j nD F nd ig miD iF nd vivermoreD F nd fowerD F @PHIRA 9w ss nd m gni( tion m ps for the ru le p e eles ope prontier pields lusters X impli tions for highEredshift studiesF9D wonthly noti es of the oy l estronomi l o ietyFD RRR @IAF ppF PTVEPVWF Further information on publisher's website: Additional information: Use policyThe full-text may be used and/or reproduc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
274
3

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 218 publications
(290 citation statements)
references
References 61 publications
13
274
3
Order By: Relevance
“…powerful gravitational lens, the system has been investigated both in the strong- (Zitrin et al 2009;Limousin et al 2012;Richard et al 2014;Diego et al 2015b) and in the weak-lensing regimes (Jauzac et al 2012;Medezinski et al 2013), further underlining its position as one of the most complex, dynamically active, and massive clusters studied to date.…”
Section: Macs J0717 In the Hubble Frontier Field Eramentioning
confidence: 99%
See 1 more Smart Citation
“…powerful gravitational lens, the system has been investigated both in the strong- (Zitrin et al 2009;Limousin et al 2012;Richard et al 2014;Diego et al 2015b) and in the weak-lensing regimes (Jauzac et al 2012;Medezinski et al 2013), further underlining its position as one of the most complex, dynamically active, and massive clusters studied to date.…”
Section: Macs J0717 In the Hubble Frontier Field Eramentioning
confidence: 99%
“…Prior to the HFF observations, 16 multiple-image systems, comprising 48 individual images, had been reported (Johnson et al 2014;Richard et al 2014;Coe et al 2015). The analysis by Diego et al (2015b), using the first third of the data from the HFF observations, identified an additional 17 multiple-image systems, as well as 10 elongated features, assumed to be single images of lensed background galaxies.…”
Section: Previous Workmentioning
confidence: 99%
“…The core and cutoff radii are poorly constrained with an Einstein ring of about 6.2 kpc at z = 1.525. We therefore choose to fix r core = 0.15 kpc (e.g., Limousin et al 2007;Richard et al 2014), and r cut = 100 kpc (e.g., Brainerd et al 1996), which are typical values for isolated galaxies. Varying these values within our observational constraints changes the mass estimate by < 10 %.…”
Section: Lens Modeling and Source Reconstructionmentioning
confidence: 99%
“…Five teams have provided amplification maps for the six HFF clusters, using different methods and assumptions on the mass models (Bradač et al 2009;Richard et al 2014;Merten et al 2011;Zitrin et al 2013;Johnson et al 2014;Mohammed et al 2014). Jauzac et al (2014) have used the Frontier Fields data to search for multiple-image objects in MACSJ0416.1−2403 data.…”
Section: Magnificationmentioning
confidence: 99%
“…The new flagship program of HST, the Frontier Fields (hereafter, HFFs) started at the end of 2013, and employs deep observations combined with gravitational lensing to observe six massive galaxy clusters along with six deep blank fields. Recent papers have shown that ultra faint galaxies (m F160W ∼31−32 AB) will be detected in HFF data (Yue et al 2014;Richard et al 2014), and that the number of z ≥ 8 objects expected in these data is > ∼ 130 (Coe et al 2015).…”
Section: Introductionmentioning
confidence: 98%